Antimalarial treatment may have a time-dependent effect on lupus survival : Data from a multinational Latin American inception cohort (2010)
ABSTRACT: Objective: To evaluate the beneficial effect of antimalarial treatment on lupus survival in a large, multiethnic, international longitudinal inception cohort. Methods: Socioeconomic and demographic characteristics, clinical manifestations, classification criteria, laboratory findings, and treatment variables were examined in patients with systemic lupus erythematosus (SLE) from the Grupo Latino Americano de Estudio del Lupus Eritematoso (GLADEL) cohort. The diagnosis of SLE, according to the American College of Rheumatology criteria, was assessed within 2 years of cohort entry. Cause of death was classified as active disease, infection, cardiovascular complications, thrombosis, malignancy, or other cause. Patients were subdivided by antimalarial use, grouped according to those who had received antimalarial drugs for at least 6 consecutive months (user) and those who had received antimalarial drugs for <6 consecutive months or who had never received antimalarial drugs (nonuser). Results: Of the 1,480 patients included in the GLADEL cohort, 1,141 (77%) were considered antimalarial users, with a mean duration of drug exposure of 48.5 months (range 6–98 months). Death occurred in 89 patients (6.0%). A lower mortality rate was observed in antimalarial users compared with nonusers (4.4% versus 11.5%; P< 0.001). Seventy patients (6.1%) had received antimalarial drugs for 6–11 months, 146 (12.8%) for 1–2 years, and 925 (81.1%) for >2 years. Mortality rates among users by duration of antimalarial treatment (per 1,000 person-months of followup) were 3.85 (95% confidence interval [95% CI] 1.41–8.37), 2.7 (95% CI 1.41–4.76), and 0.54 (95% CI 0.37–0.77), respectively, while for nonusers, the mortality rate was 3.07 (95% CI 2.18–4.20) (P for trend < 0.001). After adjustment for potential confounders in a Cox regression model, antimalarial use was associated with a 38% reduction in the mortality rate (hazard ratio 0.62, 95% CI 0.39–0.99). Conclusion: Antimalarial drugs were shown to have a protective effect, possibly in a time-dependent manner, on SLE survival. These results suggest that the use of antimalarial treatment should be recommended for patients with lupus.